1979
DOI: 10.1093/ajcn/32.5.1051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary egg on human serum cholesterol and triglycerides

Abstract: One hundred sixteen male volunteers between the ages of 32 and 62 years (mean age 46) consumed two whole fresh eggs daily in their customary diets for 3 months and also eliminated eggs for 3 months before or after eating eggs. The men had had normal-range serum cholesterol and triglycerides for the past 7 years. Four-day food records kept by them in each experimental period were assessed for nutrient intake. A Latin square design allowed analyses for season and sequential effects on serum lipids. The serum cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(36 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…In addition, a decrease of MDA-LDL and prolonged LDL oxidation lag time indicated that daily moderate egg consumption might reduce LDL oxidizability. Some studies have shown that dietary cholesterol provided by eggs does not affect cholesterol concentration (10,11). Others have indicated that egg intake increases both HDL-C and LDL-C and hence, does not affect the L/H cholesterol ratio (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a decrease of MDA-LDL and prolonged LDL oxidation lag time indicated that daily moderate egg consumption might reduce LDL oxidizability. Some studies have shown that dietary cholesterol provided by eggs does not affect cholesterol concentration (10,11). Others have indicated that egg intake increases both HDL-C and LDL-C and hence, does not affect the L/H cholesterol ratio (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of precision in regulatory responses to a dietary cholesterol challenge in the general population remains unknown. Numerous studies in free-living outpatients suggest that a majority have relatively precise feedback control mechanisms, since an increased dietary cholesterol intake fails to significantly increase plasma cholesterol levels in the majority of subjects (3,4,10,(24)(25)(26)(27)(28)(29)(30)(31). In sharp contrast to the relatively minor effect of dietary cholesterol on plasma cholesterol levels, the quality of dietary fat has been shown to have a more consistent influence on plasma lipid levels: a shift from a saturated to a mono-or polyunsaturated fat (PUFA)' diet will lower plasma cholesterol levels in the majority of subjects (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between dietary cholesterol, the relative proportions of dietary polyunsaturated to saturated fatty acids (P/S)' and plasma cholesterol levels have been extensively examined in cross-sectional population surveys (1)(2)(3)(4), in outpatients who have been instructed in various experimental diets (5)(6)(7)(8)(9)(10)(11)(12), and in metabolic ward studies (17)(18)(19)(20)(21). Cross-sectional surveys demonstrate poor correlations between reported dietary intakes and blood lipids but diets with high P/ S consistently lower cholesterol levels in outpatient and inpatient studies (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%